Tindak Tutur Asertif dalam Podcast Deddy Corbuzier yang berjudul “Ghozali Everyday NFT Kaya Mendadak? - Afni, Renni; Ningsih, Rika (UIR Press, 2025)
This study aims to describe the form of assertive speech acts in Deddy Corbuzier's podcast entitled